2020
DOI: 10.3389/fpubh.2020.00149
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital Mediates the Association Between Perceived Organizational Support and Work Engagement Among Chinese Doctors

Abstract: Background: As experts studying occupational health psychology know, low level of work engagement leads to higher turnover intentions. Some researchers have put a focus on the association between organizational support and work engagement. However, little has been done concerning the mediating effect of psychological capital (PsyCap) on the association between perceived organizational support (POS) and work engagement (vigor, dedication, absorption) among Chinese doctors. Methods:A cross-sectional study has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 56 publications
9
33
1
Order By: Relevance
“… 31 However, although some conditions for mediation were found among physicians (that is, distributive justice explained organizational commitment and turnover intention, and organizational commitment explained work engagement), work engagement did not affect physicians’ turnover intention, which inhibited the chain mediating effect. This finding is inconsistent with previous studies showing that work engagement could significantly negatively affect the turnover intention of rural physicians in China, 56 which needs further attention in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“… 31 However, although some conditions for mediation were found among physicians (that is, distributive justice explained organizational commitment and turnover intention, and organizational commitment explained work engagement), work engagement did not affect physicians’ turnover intention, which inhibited the chain mediating effect. This finding is inconsistent with previous studies showing that work engagement could significantly negatively affect the turnover intention of rural physicians in China, 56 which needs further attention in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In service sector, several studies investigated the impact of POS on employees' engagement, for example, Imran et al [60] in their study on employees from banking sector in Pakistan found that POS significantly and positively influence employees' work engagement. The same results were found in the study of Yang et al [76], who conducted their study on the Chinese doctors working in health sector in China, and also in the study conducted by Rahman et al [77] on employees of healthcare sector in Bangladesh. In other studies, this effect was found to be indirect and was associated with self-efficiency of the employees of education sector [29] and financial service sector [78].…”
Section: Pos and Employees Engagementsupporting
confidence: 82%
“…The Pearson correlation coefficient was used to evaluate the corrections among the research variables. Hierarchical regression was used to explore the mediating effect of psychological capital on the relationship between problematic smartphone use and learning burnout ( Zimet et al, 1990 ; Yang et al, 2020 ). The variance inflation factor (VIF) values were less than 10, and there was no multicollinearity in this study.…”
Section: Methodsmentioning
confidence: 99%